Acute Psychosis as Main Manifestation of Central Pontine Myelinolysis. (14th March 2017) - Gopal, Mangala; Parasram, Melvin; Patel, Harsh; Ilorah, Chike; Nersesyan, Hrachya
Abstract : Central pontine myelinolysis (CPM) is an acute demyelinating neurological disorder affecting primarily the central pons and is frequently associated with rapid correction of hyponatremia. Common clinical manifestations of CPM include spastic quadriparesis, dysarthria, pseudobulbar palsy, and encephalopathy of various degrees; however, coma, "locked-in" syndrome, or death can occur in most severe cases. Rarely, CPM presents with neuropsychiatric manifestations, such as personality changes, acute psychosis, paranoia, hallucinations, or catatonia, typically associated with additional injury to the brain, described as extrapontine myelinolysis (EPM). We present a patient with primarily neuropsychiatric manifestations of CPM, in the absence of focal neurologic deficits or radiographic extrapontine involvement. A 51-year-old female without significant medical history presented with dizziness, frequent falls, diarrhea, generalized weakness, and weight loss. Physical examination showed no focal neurological deficits. Laboratory data showed severe hyponatremia, which was corrected rather rapidly. Subsequently, the patient developed symptoms of an acute psychotic illness. Initial brain magnetic resonance imaging (MRI) was unremarkable, although a repeat MRI two weeks later revealed changes compatible with CPM. This case demonstrates that acute psychosis might represent the main manifestation of CPM, especially in early stages of the disease, which should be taken into consideration when assessing patients with acute abnormalities of sodium metabolism.